Biopsy-derived Intestinal Epithelial Cell Cultures for Pathway-based Stratification of Patients With Inflammatory Bowel Disease. (23rd September 2017) - Vanhove, Wiebe; Nys, Kris; Arijs, Ingrid; Cleynen, Isabelle; Noben, Manuel; De Schepper, Sebastiaan; Van Assche, Gert; Ferrante, Marc; Vermeire, Séverine
Abstract: Background: Endoplasmic reticulum [ER] stress was shown to be pivotal in the pathogenesis of inflammatory bowel disease. Despite progress in inflammatory bowel disease [IBD] drug development, not more than one-third of patients achieve steroid-free remission and mucosal healing with current therapies. Furthermore, patient stratification tools for therapy selection are lacking. We aimed to identify and quantify epithelial ER stress in a patient-specific manner in an attempt towards personalised therapy. Methods: A biopsy-derived intestinal epithelial cell culture system was developed and characterised. ER stress was induced by thapsigargin and quantified with a BiP enzyme-linked immunosorbent assay [ELISA] of cell lysates from 35 patients with known genotypes, who were grouped based on the number of IBD-associated ER stress and autophagy risk alleles. Results: The epithelial character of the cells was confirmed by E-cadherin, ZO-1, and MUC2 staining and CK-18, CK-20, and LGR5 gene expression. Patients with three risk alleles had higher median epithelial BiP-induction [vs untreated] levels compared with patients with one or two risk alleles [ p = 0.026 and 0.043, respectively]. When autophagy risk alleles were included and patients were stratified in genetic risk quartiles, patients in Q2, Q3, and Q4 had significantly higher ER stress [BiP] when compared with Q1 [ p = 0.034, 0.040, and 0.034, respectively]. Conclusions: We developed and validated an ex vivo intestinal epithelial cell culture system and showed that patients with more ER stress and autophagy risk alleles have augmented epithelial ER stress responses. We thus presented a personalised approach whereby patient-specific defects can be identified, which in turn could help in selecting tailored therapies.